Analisis Potensi Industri Halal bagi Pebisnis Kuliner di Indonesia - Mohammad habibi (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
This study aims to analyze the potential of industrial halal cullinary products for business actors in Indonesia, this is considering to halal products experience rapid development in the midst of increasing religious tendency of Indonesian society and on the other side of the Muslim population in the middle class have increased revenue, resulting in demand for products halal is also increasing. The data used in this study is secondary data sourced from several publications of goverment agencies with the analytical tools used are qualitative descriptive. This study found the potential of halal industry for business actors in Indonesia, among others: First, the need for Halal Products (goods and services). Second, Halal Product Diversity. Third, the completeness of the Legal Framework. Fourth, Many Business Executors in Halal Product Market. Fifth, Halal Cullinary Product Society Needs and Export. Keywords: Industrial Potential, Halal Cullinary Product, Business Actor